33. A rare case of Guillain–Barre' syndrome and pseudotumor cerebri, with normal cerebrospinal fluid protein. Issue 4 (April 2016) - Stipa, G.; Caproni, S.; Moschini, E.; Sensidoni, A.; Frondizi, D.; Di Schino, C.; Galletti, F.; Di Chirico, A.; Rossi, V.; Mancini, A.; Roscini, N.; Carletti, S.
Abstract : A 19 years old female patient was referred for assessment of head and cervical pain, upper limbs dysesthesias, diplopia, visual impairment (mainly in left eye) and postural instability. Initial examination revealed left ptosis, left abducent nerve palsy, diffuse hyporeflexia and limb ataxia. At admission lumbar puncture was performed with a normal cerebrospinal fluid analysis and a temporal dispersion of F waves and Skin Reflex was observed by electromyography. In suspicion of a Guillain–Barré syndrome a IV immunoglobulin treatment was administered. In first days after admission a progression of sings and symptoms was observed; a left peripheral facial palsy was also noted. In particular, the visual acuity decreased in both eyes (5/10 at right, 1–2/10 at left), severe bilateral papilledema and increased optic nerves diameters (7.4 mm at left) were revealed. Brain and spine MRI was unremarkable. Thus, through a second lumbar puncture a cerebrospinal fluid pressure of 25 mmHg was measured. In light of this 10 cc of cerebrospinal fluid were subtracted and high dosage escalating diuretic treatment (mannitol, steroid, acetazolamide and topiramate) was administrated. A further slow improvement of motor and visual signs and symptoms was observed. At discharge the patient referred a complete remission of headache and dysesthesias.